2023
DOI: 10.1101/2023.01.31.23285251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome 10q24.32 Variants Associate with Brain Arterial Diameters in Diverse Populations: A Genome-Wide Association Study

Abstract: Background: Brain arterial diameters are novel imaging biomarkers of cerebrovascular disease, cognitive decline and dementia. Traditional vascular risk factors have been associated with brain arterial diameters but whether there may be genetic determinants of brain arterial diameters is unknown. Results: We studied 4150 participants from six geographically diverse population-based cohorts (40% European, 14% African, 22% Hispanic, 24% Asian ancestries). We measured brain arterial diameters for 13 segments and a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…NT5C2 is located at 10q24.32, which has been reported as a highlight locus of autism spectrum disorder, brain arterial diameters, and schizophrenia [91][92][93] . A previous study in zebrafish found NT5C2 as a potential causal gene in this region for blood pressure 94 .…”
Section: Discussionmentioning
confidence: 99%
“…NT5C2 is located at 10q24.32, which has been reported as a highlight locus of autism spectrum disorder, brain arterial diameters, and schizophrenia [91][92][93] . A previous study in zebrafish found NT5C2 as a potential causal gene in this region for blood pressure 94 .…”
Section: Discussionmentioning
confidence: 99%